Артритогенное действие интерлейкина-6 при периодической болезни - З. Т. Джндоян (Հայաստանի ԳԱԱ)
ՊՀ-ը ինքնաբորբոքային ժառանգական հիվանդություն է, որը փոխանցվում է աուտոսոմ-ռեցիսիվ ճանապարհով և ախտահարում է որոշ էթնիկական խմբերի ներկայացուցիչներին: ՊՀ բնորոշ ախտանիշներից է արթրոպաթիան: Արտահայտված հոդային համախտանիշը հայտնաբերվել է մեր հետազոտած հիվանդների 87%–ի մոտ: Familial Mediterranean fever is an autoinflammatory autosomal recessive disease with definite ethnic predisposition. Arthropathy is the typical symptom for FMF. Severe joint syndrome was established in 87% of our FMF patients, and more frequent mutations of MEFV gene among these patients were the M694V/V726A and М694V/M69V ones. FMF is characterized mainly by lesion of large joints, rarely of small joints, with joint pain and limitation of the movements.
Keywords: Medicine; Pathology